Nutritional status and its effect on dental health among children - Alanazi, Hend A.; Alenazi, Huda K.; Alenazi, Seham N.; Alotaibi, Noura H.; Alanazi, Khulud B.; Alqahtani, Ahmed S.; Alosaimi, Yasser O. (International Journal Of Community Medicine And Public Health, 2022)
Nutritional status has a significant role in oral health and disease. Protein deficiency is the key deficiency in intermediate malnutrition. Malnutrition can disrupt homeostasis, resulting in disease progression of the oral cavity, decreased resistance to microbial biofilm, and decreased tissue healing capacity. This paper examines the association between malnutrition, protein-energy malnutrition, and dental health. Malnutrition is a risk factor for several dental diseases, such as dental caries and periodontal diseases. Studies have suggested that enamel hypoplasia, salivary gland hypofunction, and compositional changes in the saliva may be the mechanisms through which malnutrition is associated with caries. The exfoliation and eruption of teeth are impacted by malnutrition, or protein energy malnutrition (PEM), starting in the early years and continuing throughout infancy. The risk of hypoplasia was higher in malnourished children. The development of hypocalcemia as a result of diarrhoea in chronic undernutrition may explain the link between PEM and poor enamel formation. Deficiencies of vitamins A, C, and D are found to be associated with hypoplasia. Protein-deficit malnutrition and low vitamin D levels, as well as obesity, are risk factors for dental caries in children. Early childhood malnutrition affects salivary gland hypofunction and compositional changes in the saliva, and these might be the mechanisms through which malnutrition is associated with caries. Early childhood protein-energy malnutrition (ECPEM) is associated with poor periodontal status and causes cancrum oris, necrotizing gingivitis, and other periodontal disease conditions, as well as symptoms that mimic periodontal conditions.